HARMONISASI HUKUM PENGANGKATAN ANAK DALAM DESA ADAT DI BALI (SUATU KAJIAN PLURALISME HUKUM) - Ni Ketut Kantriani; Ida Bagus Sudarma Putra (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Offspring is expected in marriage, in Hinduism the purpose of marriage, namely in the book of Manawa Dharmasastra, mentioned that praja (giving birth to offspring). But in reality in marriage not all the wishes that are expected will be achieved. In Bali marriages that do not have children generally perform the rapture of children. According to Balinese customary law the removal of children is generally a child who is raised from the purusha line (from the male lineage), the purpose of the child's rapture is to continue the offspring, responsibility in the form of rights and obligations. The appointment of children for a Hindu married couple who are Balinese, Then the implementation of the child appointment process should follow the provisions of Hindu law, then Balinese customary law (awig-awig and pararem) that applies in each customary village in addition to also still referring to the process of child adoption procedures that have been regulated in the applicable legislation in Indonesia. Based on this background, the issues discussed can be formulated as follows: 1. How to regulate the shahnya rapture of children according to customary law, Hinduism and National Law. 2. How the process of carrying out the appointment of children in indigenous villages in Bali is studied from legal pluralism. concepts: harmonization of law, adoption of children, pluralism of law, theory using legal pluralism (John Griffiths) and living law theory (Eugene Ehrlich), type of empirical legal research, descriptive nature of research, type of data qualitative and sourced from primary data and secondary data, using methods of data collection, obsenvation, interview, and literature. Determination of informants using non probability sampling, the instrument used by mobile phones, management and qualitative and systematic descriptive analysis. The results of research 1) The regulation of the shahnya child appointment can be seen from 3 legal bases, namely national law, customary law, and religious law. 2) In the process of carrying out the adoption of children in indigenous villages in Bali on the point of view of legal pluralism, namely the combination of three basic legal rules, including national law, customary law (awig-awig and pararem), and religious law (Hindu law), where the three legal bases run simultaneously in the implementation of child adoption in harmony, and balance, so as to create a harmony of law in the implementation of child appointment in indigenous villages in Bali